A Competitiveness Analysis of Thai Chicken Eggs in the Hong Kong Market - Wichai, Taechawattananan (2008)
Today, the chicken egg industry in Thailand has become one of the major livestock components and been mainly produced for domestic consumption, accounting for nearly 98 percent of the country's production. Although the quantity of chicken egg exports has been approximately two percent of the country's production, it has been significantly proven to solve the problem of the imbalance between the supply and demand, which causes price and farmers' income instability. Thailand has exported chicken eggs to many countries, but Hong Kong has been the highest importing country that shares nearly 80 percent of the country's exports with the annual growth of more than 50 percent. Thus, it is not exaggeration to say that Hong Kong is the most important market for Thai chicken egg exports. Thailand has become an increasingly important exporter in the Hong Kong market and value and quantity of chicken egg exports to this market have been continuously increasing, but both value and quantity have fluctuated due to facing some fundamental challenges of a strong competition from the other three competitors; i.e. China, Germany and USA who are the top three exporting countries and attempt to assume a more active role as major players of the egg market in the Hong Kong market. Thus, the main objectives of this study focused on: first, the measurement of revealed comparative advantage and the evaluation of competitive position of Thai chicken eggs in the Hong Kong market as compared to those of the other three competitors; second, an analysis of the import prices of Thai chicken eggs in the Hong Kong market as compared to those of the other three competitors; third, providing the policymakers and producers with the current background information and statistics required; fourth, developing the strategic approaches to improve the competitiveness of Thai chicken eggs in the Hong Kong market; lastly, addressing the issues arising from government policies and industry strategies for the competitive performance of the Thai chicken egg exports. In order to achieve the objectives of the study, the methods of reveal comparative advantage index, brand switch analysis, and qualitative and quantitative price analysis were used to measure and examine the reveal comparative advantage of Thai chicken eggs in the Hong Kong market, to evaluate the competitive position of Thai chicken eggs in the Hong Kong market, and to analyze the import price of Thai chicken eggs in the Hong Kong market, respectively. The results of the study can be concluded that from 1995 to 2005, Thai chicken eggs were still competitive in the Hong Kong market, but China chicken eggs had the highest competiveness in the market, followed by USA's, Germany's and Thailand's.